A Novel Base‐Induced Isomerization Gives Access to Unprecedented (E)‐exo‐Glycals. Issue 35 (25th July 2013) - Eppe, Guillaume; Dumitrescu, Lidia; Pierrot, Olivier; Li, Tianlei; Pan, Weidong; Vincent, Stéphane P.
<x xml:space="preserve">Abstract</x> Bump the base: This study reports the discovery of the base‐induced Z‐to‐E isomerization of exo‐glycals bearing an electron‐withdrawing group (EWG). The scope of this novel transformation regarding the carbohydrate unit is also discussed. After elucidating the mechanism, preparation of novel (E)‐exo‐ glycals was performed (TBS=tert‐butyldimethylsilyl).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>